Ternary system cationic copolymer (dimethylaminoethyl methacrylate: Butyl methacrylate)/thioglycolic acid doped copper tungstate nanocomposite for environmental remediation and pathogen control supported by molecular docking analysis - Mohamed Kadie, Abdikani Hussein; Haider, Ali; Shahzadi, Anum; Ul-Hamid, Anwar; Ullah, Hameed [UNESP]; Ayari-Akkari, Amel; Mateen, Zernab; Ikram, Muhammad (Elsevier, 2025)
2 and 4 wt % of cationic copolymer (dimethylaminoethyl methacrylate: butyl methacrylate) designed eudragit (Eud) with a fixed quantity of thioglycolic acid (TGA) doped copper tungstate (CuWO4) nanocomposite (NC) were prepared using a co-precipitation approach. A range of characterization techniques was employed to analyze the structural, optical, and compositional characteristics of prepared NC. XRD analysis confirmed the monoclinic and anorthic crystal structure of CuWO4, addition of Eud and TGA resulted in increased crystallinity of CuWO4. FTIR spectra verified the presence of vibrational modes related to CuWO4. The electronic spectra demonstrated an increased absorption window and redshift with Eud and TGA, leading to the reduction in bandgap energy (Eg). FESEM analysis elucidates the flakes and rod-like structures on the surface of CuWO4 with dopants. 4 wt % Eud/TGA-CuWO4 revealed a significant reduction of methyl orange (MO) dye in a neutral medium. Furthermore, the bactericidal effectiveness was tested against S. aureus, demonstrating a remarkable inhibition zone (7.35 mm). The mechanism behind the bactericidal action of TGA-CuWO4, Eud/TGA-CuWO4 NC against DNA gyrase S. aureus (Gram + ve) was studied using molecular docking.
Keywords: Co-precipitation; Dye decolorization; Molecular docking; S. aureus